2022
DOI: 10.3389/fmicb.2022.865001
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir Treatment for Influenza During the Flu Season of 2018–2019: A Longitudinal Study

Abstract: BackgroundOseltamivir resistance in influenza virus (IFV) has been of widespread concern. An increase in the frequency of viruses with reduced inhibition was observed. Whether oseltamivir is effective is uncertain. We conducted this study to understand the real-world situation in northern China and the clinical efficacy for patients with IFV infection after the use of oseltamivir.MethodsThe longitudinal study was performed on influenza-like illness (ILI) cases in a tertiary general hospital in Beijing, China d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Three studies reported on the duration of influenza symptoms [ 42 44 ]. The median duration of symptoms in adults with influenza-like illness ranged from 2 to 7 days [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported on the duration of influenza symptoms [ 42 44 ]. The median duration of symptoms in adults with influenza-like illness ranged from 2 to 7 days [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tsuzuki et al . noted no differences in symptom duration between vaccinated and unvaccinated patients [ 44 ], while Li et al reported duration of cough ranged from 5 to 6 days and fever from 1 to 3 days, with no differences between influenza-like illness (ILI) and influenza patients who received antiviral and supportive therapies [ 42 ].…”
Section: Resultsmentioning
confidence: 99%